Missing the mark?;women and the millennium development goals in afri. (DEMETER Press, 2016)
In the year 2000, United Nations world leaders set out eight targets, the UN Millennium Development Goals, for achieving improved standards of living at the micro level in poorer nations around the globe, by the year 2015. The papers in this collection present fine-detailed ethnographic studies of cultures in Africa and Oceania, with a focus primarily on MDG 3, targeted to ""promote gender equality and empower women"" and MDG 5, targeted to ""improve maternal health"" to ascertain whether or not these goals have made or missed their mark. Ethnographic case studies located in Solomon Islands, M.